Nanomaterial-based encapsulation of biochemicals for targeted sepsis therapy - Zhiwei Li; Bin Luo; Yisheng Chen; Lingling Wang; Yezi Liu; Jintong Jia; Mengsi Chen; Shuting Yang; Haojun Shi; Lihua Dai; Lei Huang; Changmin Wang; et al. (Materials Today Bio, 2025)
Sepsis is a life-threatening condition characterized by complex pathophysiology, including dysregulated immune responses, excessive inflammation, and oxidative stress, often leading to multi-organ failure and high mortality rates. Traditional therapies, such as antibiotics and anti-inflammatory agents, face significant limitations due to issues like drug resistance and inadequate immune modulation. Recent advancements in nanotechnology have introduced innovative solutions by leveraging nanomaterial-based encapsulation systems for bioactive substances, including antioxidants, anti-inflammatory agents, and immunomodulators. These systems enhance the stability, bioavailability, and targeted delivery of therapeutic agents, addressing critical challenges in sepsis management. Key nanocarriers, such as lipid nanoparticles, polymer-based systems, and plant-derived exosomes, offer controlled release mechanisms and precise targeting capabilities, enabling superior therapeutic outcomes. Moreover, nanomaterials' multifunctional properties allow for simultaneous modulation of oxidative stress, inflammation, and immune responses, presenting a synergistic approach to sepsis therapy. However, challenges persist, including the potential toxicity of nanomaterials, scalability of production, and hurdles in clinical translation. This review comprehensively explores the transformative potential of nanotechnology in reshaping sepsis treatment strategies, highlighting its role in advancing precision medicine and its prospects for overcoming current therapeutic barriers.